Empirical Study of Community Interest to Islamic Insurance - Kuat Ismanto; Nalim . (Institute for Research and Community Empowerment (LPPM TAZKIA), 2019)
This research explained the factors which influence people's interest to join sharia insurance customers. There were four factors which have been determined in this research, and would be tested, namely sharia compliance, insurance needs, information, and ease to get information. The research data was collected through questionnaires which randomly distributed to communities who agreed to film it and did not join insurance. Questionnaires which collected were selected according to criteria. There were 146 scattered questionnaires were selected to be 101. Data were analyzed by logistic regression, which included simultaneous testing, model accuracy test, and partial test. The findings of this study show that, four independent variables, only two variables which have a significant influence on people's interest in becoming a sharia insurance participant. These two factors are sharia compliance and insurance needs. These two significant factors indicate that people want economic motive and religion motive walk together in Islamic insurance. Two other factors, information and ease of information, do not have a significant influence on interest. The results of this study have implications for Islamic insurance companies to be able to be consistent and innovative in presenting products that meet insurance needs and maintain sharia compliance.